NUMERICAL STUDY ON THE ABNORMAL SURGE DUE TO ATMOSPHERIC PRESSURE VARIATION ON THE CENTRAL COAST OF VIETNAM - Thuy, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2019)
In this study, the abnormal surge due to atmospheric pressure variation assumed to travel to the Central coast of Vietnam was simulated in some scenarios of maximum atmospheric variation (Pmax), the size (L) and the speed of the movement (Cp) of the atmospheric disturbance. The numerical model is based on two-dimensional long wave model considering the effect of atmospheric pressure variation on the sea level. The results showed that the surge height at the coastal area incresed as the size and maximum atmospheric variation of disturbance pressure increased. In which, when the traveling speed of atmospheric disturbance increased, the surge height increased, reaching to the maximum value of 0.72 m at Cp = 45 km/h, then decreasing. Meanwhile, the wave period decreased gradually to Cp = 30 km/h and was then almost unchanged. The coastal area around the latitude of 13oN was noted to have a higher surge level than both sides that may be due to the high steep of coastal topography. The results of the study are significant in investigation into the reason of abnormal surge in the area as well as serving the planning and disaster preparedness.